A functional PTPN22 polymorphism associated with several autoimmune diseases is not associated with IgA deficiency in the Spanish population - Fernández-Arquero Miguel; García-Rodríguez M Cruz; Martínez Alfonso; López-Mejías Raquel; Núñez Concepción; de la Concha Emilio G; Urcelay Elena (BMC, 2006)
Abstract Background The 1858C/T SNP of the PTPN22 gene has been associated with many autoimmune diseases, suggesting the existence of an inflammatory process common to all of them. We studied the association of that polymorphism with immunoglobulin A deficiency (IgAD) following a double approach: a case-control and a TDT study. Methods A total of 259 IgAD patients and 455 unrelated matched controls, and 128 families were used for each approach. Comparisons were performed using Chi-Square tests or Fisher's exact test when necessary. Results No association between the PTPN22 1858C/T SNP and IgA deficiency was found in any case (allelic frequencies 8% vs. 6% in patients and controls, respectively, OR= 1.14 (0.72-1.79), p= 0.56; TDT p = 0.08). Conclusion The result obtained seems to reinforce the consideration of IgA deficiency as a primary immunodeficiency rather than an autoimmune disease.